2012
DOI: 10.1063/1.3679380
|View full text |Cite
|
Sign up to set email alerts
|

Extracting accurate capacitance voltage curves from impedance spectroscopy

Abstract: We propose a method to obtain accurate capacitance-voltage (C-V) curves in the presence of multiple space charges. This method uses impedance spectroscopy to evaluate individual space charges separately. The advantage is that the knowledge of the exact equivalent circuit is not essentially needed. The comparison with other methods to calculate the doping concentration NA shows that our method is unaffected by series resistances and agrees best with the correct value of NA. The evaluation of the impedance spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The barrier height on the control sample is 0.59 eV, which is in agreement with the historical value for Al on p-type Si, 0.58 eV [13]. The barrier height can also be determined with C-V measurements, in which the capacitance of a sample is determined through the measured impedance using a suitable equivalent circuit [15]. However, it has been shown that C-V measurements with a single alternating-current (AC) frequency often produce inaccurate results, and multiple-frequency measurements should be used to account for series resistances [16].…”
Section: A Al/s-passivated N-type Si(100) Junctionssupporting
confidence: 54%
See 1 more Smart Citation
“…The barrier height on the control sample is 0.59 eV, which is in agreement with the historical value for Al on p-type Si, 0.58 eV [13]. The barrier height can also be determined with C-V measurements, in which the capacitance of a sample is determined through the measured impedance using a suitable equivalent circuit [15]. However, it has been shown that C-V measurements with a single alternating-current (AC) frequency often produce inaccurate results, and multiple-frequency measurements should be used to account for series resistances [16].…”
Section: A Al/s-passivated N-type Si(100) Junctionssupporting
confidence: 54%
“…5 yield the C-V curve and thus the barrier height for the front Al contact [15]. The capacitance is extracted from the maxima using the following equations [15] = −2 (2)…”
Section: B Al/s-passivated P-type Si(100) Junctionsmentioning
confidence: 99%
“…Subsequently, possible deviations from this ideal relationship are discussed. Also the publication of Guenther et al [59], that introduces a more re ned approach of extracting the actual capacitance of the depletion layer from the immittance data, does ignore the contribution of defects (though, they assume that their approach should still work when defects are recognised). system are dominated by defects at the interface or in the insulator.…”
Section: Insights From Conventional Capacitance-voltage Analysismentioning
confidence: 99%
“…To extract the capacitance for a subsequent capacitance-voltage analysis, it is quite common to interpret the system as a two component circuit consisting of one resistor and one capacitor [59]. There are two possible arrangements of the circuit elements: in series or parallel.…”
Section: Differences To the Conventional Characterisation Of Mos Stru...mentioning
confidence: 99%
See 1 more Smart Citation